Evaluation of the Garut Regency National Health Insurance Program - Ikeu Kania (Budapest International Research and Critics University, 2021)
The purpose of this study was to evaluate the National Health Insurance Program at the Garut Regency level. This study uses a mixed-method with a perception survey approach conducted on the quality of the National Health Insurance program in the Garut district. The sources of data in this study are primary data and secondary data. The data collection technique used is the questionnaire method with a data collection range of January-February 2021 with the questionnaire method and in-depth interviews. The unit of analysis in this study is the service provided to patients at the First Level Health Facility in Garut district. Determination of the sample using purposive random sampling method with criteria as patients who receive tiered referral services. Based on the results of research and analysis, it can be seen that: 1) The evaluation of the National Health Insurance program at the Garut Regency level is considered quite good with an index value of 3.05 (Enough), and the service model achievement indicator obtains an index value of Enough; 2) Based on the results of interviews with respondents, it shows that there are several health service problems, including the lack of understanding of the participants of the Health Social Security Administering Body on the service procedures applied, the socialization of the program has not been thoroughly carried out to the community; and 3) The service quality of the Health Social Security Administering Body in Garut district is considered quite good.